Cr(VI) Removal from Wastewater by Using Rice Husk Ash (RHA) - M. J. Uddin; M. M. R. Khan; M. S. Iftekhar; M. A. Islam (ASEAN Journal of Chemical Engineering, 2006)
Rice husk ash (RHA) was studied as a potential adsorbent for Chromium (VI)removal from wastewater. RHA was able to remove effectively and economically toxic metal from synthetic wastewater. Experiments were done on the removal of Cr(VI) from dichromate solution which is a form of chromium in tannery effluent. The amount of Cr(VI) adsorption increased with the decrease in pH. The optimum parameter was = 2.0 evaluated at pH and the dose rate of the adsorbent was 5 kg RHNm3. The equilibrium data fit well in both the Langmuir and Freundlich isotherms. The study showed that 89.29 x 10-3kg Cr(VI) could be removed by 1 Kg of RHA. Since rice husk (RH) is available and cheap in Bangladesh, it can be used easily as an appropriate adsorbent to remove more than 95% Cr(VI) from tannery wastewater.